International association of agricultural librarians and documentalists (IAALD) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
International association of agricultural librarians and documentalists (IAALD)IAALD, a non-profit making association was founded in 1955 . The aims of the association are to promote, internationally and nationally, agricultural library science and...